a)[tex]\vec{AB} = (4-1)\vec{i} + (7-3)\vec{j} = 3\vec{i} + 4\vec{j}[/tex]
[tex]|\vec{AB}| = \sqrt{3^2+4^2} = \sqrt{9 + 16} = \sqrt{25} = 5[/tex]
b)[tex]\vec{AB} = (-1-2)\vec{i} + (4-8)\vec{j} = -3\vec{i} - 4\vec{j}[/tex]
[tex]|\vec{AB}| = \sqrt{(-3)^2+(-4)^2} = \sqrt{9 + 16} = \sqrt{25} = 5[/tex]
c)[tex]\vec{AB} = (3-1)\vec{i} + (4-0)\vec{j} = 2\vec{i} + 4\vec{j}[/tex]
[tex]|\vec{AB}| = \sqrt{2^2+4^2} = \sqrt{4 + 16} = \sqrt{20} = 2\sqrt{5}[/tex]
d)[tex]\vec{AB} = (2-2)\vec{i} + (5-(-1))\vec{j} = 6\vec{j}[/tex]
[tex]|\vec{AB}| = \sqrt{6^2} = \sqrt{36} = 6[/tex]